Extending the Cultivation Area of Pecan (Carya illinoinensis) Toward the South in Southeastern Subtropical China May Cause Increased Cold Damage - Zheng, Jinbin; Hänninen, Heikki; Lin, Jianhong; Shen, Sitian; Zhang, Rui (Frontiers in Plant Science, 2021)
Pecan (Carya illinoinensis) is an important nut tree species in its native areas in temperate and subtropical North America, and as an introduced crop, in subtropical southeastern China as well. We used process-based modelling to assess the effects of climatic warming in southeastern China on the leafout phenology of pecan seedlings and the subsequent risk of ‘false springs’. In order to maximize the biological realism of the model used in the scenario simulations, we developed the model on the basis of experiments explicitly designed for determining the responses modelled. The model showed reasonable internal accuracy when calibrated against leafout observations in a whole-tree chamber (WTC) experiment with nine different natural-like fluctuating temperature treatments. The model was used to project the timing of leafout in 2022 – 2099 under the warming scenarios RCP4.5 and RCP8.5 in southeastern China. Two locations in the main pecan cultivation area in the northern subtropical zone and one location south from the main cultivation area were addressed. Generally, an advancing trend of leafout was projected for all three locations under both warming scenarios, but at the southern location a delay was projected under RCP8.5 in many years during the first decades of the 21st century. At the two northern locations, cold damage caused by false springs was projected to occur once in 15 – 26 years at the most, suggesting that pecan cultivation can be continued relatively safely at these two locations. Paradoxically, more frequent cold damage was projected for the southern location than for the two northern locations. The results for the southern location also differed from those for the northern locations in that more frequent cold damage was projected under the RCP4.5 warming scenario (once in 6 years) than under the RCP8.5 scenario (once in 11 years) in the southern location. Due to the uncertainties of the model applied, our conclusions need to be re-examined in additional experimental work and further model development based on it; but based on our present results, we do not recommend starting large-scale pecan cultivation at locations south of the present main pecan cultivation area in south-eastern subtropical China.